Article Review: Congenital Nasolacrimal Duct Obstruction With Massage Therapy of The Lacrimal Sac - Farraz Kanya Syahra; Rani Himayani; Putu Ristyaning Ayu Sangging (CV. Jasa Sukses Abadi, 2023)
Nasolacrimal duct obstruction is a disorder that is often found in children at the early age of birth. In most cases, the obstruction lies distal to the nasolacrimal duct as a result of a patent Hasner's valve. Epidemiological studies report that the prevalence of congenital nasolacrimal duct obstruction ranges from 5% to 20% in early childhood. Clinical manifestations that can occur as a result of this obstruction are in the form of epiphora or tears that don't drain properly resulting in accumulation and overflow of tears. In addition, symptoms that arise can be erythema on the periorbital skin, upper and lower eyelids due to irritation originating from reflex rubbing due to teardrops and discharge with inadequate drainage. This case can be given conservative therapy in the form of massage of the lacrimal sac which has been proven in many studies with favorable results. This therapy can be given in the absence of further complications such as mucocele or dacryocystitis. Massage therapy used since 1923 is the Crigler Technique. There is a new technique devised by a pediatric ophthalmologist, Philip, who provides new information based on his experience. This writing uses the article review method using several sources obtained from journals and books. This paper aims to determine the understanding and conservative management of congenital nasolacrimal duct obstruction so that the obstruction will disappear and prevent further complications.